SOCIAL RESEARCH MATTERS : A life in family sociology - Brannen, Julia, author (Bristol, UK : Bristol University Press, 2019)
From the vantage point of forty years in social research and the study of families, the author of this book offers an invaluable account of how research is conducted and `matters' at particular times. The book has two main themes that are interwoven throughout the text. A central theme is how social research matters in relation to historical context. A second theme focuses on the practice of social research; research is a craft that is learned with and from others as well as through reading methodological texts and training.